2020
DOI: 10.3390/su12198183
|View full text |Cite
|
Sign up to set email alerts
|

Does Integrated Reporting Enhance the Value Relevance of Information? Evidence from Sri Lanka

Abstract: This paper examines the relationship between the level of integrated reporting (IR) based on the extent of adoption of the International Integrated Reporting Framework (IIRF) and the firm value (a proxy for value relevance of IR) in Sri Lanka, where the adoption of IR is a voluntary exercise. Using a comprehensive disclosure checklist, 117 integrated reports were content-analyzed, and then two regression models assessed the value relevance of IR disclosure. The study notes an increasing trend toward the adopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 68 publications
1
30
2
Order By: Relevance
“…Intending to identify the coverage of and trends in IR in Sri Lanka over a period of time, the study selected all the companies listed on the Colombo Stock Exchange for the financial JFRA 20,3/4 years ranging from 2015/2016 to 2017/2018. The annual reports for the analysis were selected from 2015 [2], as previous scholars such as Cooray et al (2020b) and Gunarathne and Senaratne (2017) confirmed that Sri Lanka had experienced a significant increase in the number of IR adopters since 2015. To maintain consistency and comparability, the companies that had prepared an integrated report throughout the three years were selected for the analysis.…”
Section: Research Methods 41 Sampling and Selection Of Integrated Rep...mentioning
confidence: 99%
“…Intending to identify the coverage of and trends in IR in Sri Lanka over a period of time, the study selected all the companies listed on the Colombo Stock Exchange for the financial JFRA 20,3/4 years ranging from 2015/2016 to 2017/2018. The annual reports for the analysis were selected from 2015 [2], as previous scholars such as Cooray et al (2020b) and Gunarathne and Senaratne (2017) confirmed that Sri Lanka had experienced a significant increase in the number of IR adopters since 2015. To maintain consistency and comparability, the companies that had prepared an integrated report throughout the three years were selected for the analysis.…”
Section: Research Methods 41 Sampling and Selection Of Integrated Rep...mentioning
confidence: 99%
“…Moderating and mediating variables included in prior researchThree studies(Omran et al, 2020;Landau et al, 2020;Cooray et al, 2020a) examine the contingent factors that interact with <IR>. This accounts for 18% of the sample studies (Table…”
mentioning
confidence: 99%
“…IR entails a new and innovative approach to current corporate reporting practices (Adams & Simnett, 2011;Nicolo et al, 2020). It combines the most material financial and non-financial information currently reported in separate reporting strands into a coherent whole (i.e., through an integrated report) and explains how they affect the ability of an organisation to create and sustain value in the short, medium, and long terms (Cooray et al, 2020;IIRC, 2011;Tlili et al, 2019). Thus, IR aims to develop a holistic corporate-reporting model (Camodeca et al, 2018;Eccles & Krzus, 2010) which depicts inter-connectivity between a firm's strategies and performance and the economic, social and environmental contexts within which it operates.…”
Section: The Concept Of Integrated Reporting (Ir)mentioning
confidence: 99%